2015
DOI: 10.14260/jemds/2015/1031
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Papanicolaou Stain [Pap] With Rapid Economic Acetic Acid Papanicolaou Stain (Reap) in Cervical Cytology

Abstract: INTRODUCTION:The present comparative study of PAP and REAP stain was carried out to assess the quality of staining, duration of staining, cost effectiveness and preservation of staining. MATERIALS AND METHODS:A total of 200 samples were studied over a period of 2 years. The pap smears were obtained from the obstetrics and gynecology out-patient department, fixed in 95% ethyl alcohol and stained simultaneously by both the methods in the department of cytology. RESULTS: Pap stain showed 2 cases (1%) of sub optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Excellent slide preservation for 2 years with considerable reduction in time and cost associated with the REAP staining method was also documented by Deshpande et al . [ 2 ] Similarly study by Shabnam Izhar reported that the REAP technique is a simple, rapid and economical technique that could be used in places with restricted resources but not for research purpose. [ 1 ] In their study of 737 cervical smears, excellent cytomorphological details were observed in 91.6% cases with the use of conventional staining and only in 33.6% cases with REAP staining.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Excellent slide preservation for 2 years with considerable reduction in time and cost associated with the REAP staining method was also documented by Deshpande et al . [ 2 ] Similarly study by Shabnam Izhar reported that the REAP technique is a simple, rapid and economical technique that could be used in places with restricted resources but not for research purpose. [ 1 ] In their study of 737 cervical smears, excellent cytomorphological details were observed in 91.6% cases with the use of conventional staining and only in 33.6% cases with REAP staining.…”
Section: Discussionmentioning
confidence: 99%
“…Various other modifications were introduced aiming to reduce the cost and time involving the procedure. [ 2 ] Rapid economical acetic acid Pap (REAP) stain is one such modified staining procedure introduced by Shabnam Izhar et al . [ 1 ] The aim of this study is to compare REAP technique over conventional staining technique to interpret their efficacy and determine cytological differences in patients with different habits.…”
Section: Introductionmentioning
confidence: 99%